Phylogeography of Paramuricea: The Role of Depth and Water Mass in the Evolution and Distribution of Deep-Sea Corals - Quattrini, Andrea M.; Herrera, Santiago; Adams, J. Mike; Grinyó, Jordi; Allcock, A. Louise; Shuler, Andrew; Wirshing, Herman H.; Cordes, Erik E.; McFadden, Catherine S. (Frontiers in Marine Science, 2022)
The processes that control diversification and speciation in deep-sea species are poorly known. Here, we analyzed data produced by Restriction-Site Associated DNA Sequencing (RAD-Seq) of octocorals in the genus Paramuricea to elucidate diversification patterns and examine the role of environmental gradients in their evolution. The genus Paramuricea evolved around 8 MYA, with a high probability of a broad ancestral depth range from mesophotic depths to the deep sea. At around 1-2 MYA, the genus diversified across the continental slope of the deep North Atlantic, supporting the depth-differentiation hypothesis, with no invasions back into shallower depths (< 200 m). Diversification in the deep sea generally occurred from shallower, warmer waters to deeper, colder depths of the lower continental slope. We also found that the vertical structure of water masses was influential in shaping phylogeographic patterns across the North Atlantic Ocean, with clades found in either upper/intermediate or intermediate/deep water masses. Our data suggest that species diverged first because of environmental conditions, including depth, temperature, and/or water mass, and then diversified into different geographical regions multiple times. Our results highlight the role of the environment in driving the evolution and distribution of Paramuricea throughout the deep sea. Furthermore, our study supports prior work showing the utility of genomic approaches over the conventionally-used DNA barcodes in octocoral species delimitation.